Aplikasi Metode Forest Health Monitoring dalam Penilaian Kerusakan Pohon di Hutan Kota Metro (Application of Forest Health Monitoring Method in Assessing Tree Damage in Metro Urban Forests) - Abimanyu, Bondan; Safe'i, Rahmat; Hidayat, Wahyu (Department of Forestry, Faculty of Agriculture, University of Lampung, 2019)
The assessment of tree condition is very important to ensure visitor safety and to maintain the sustainability of Metro Urban Forest. However, data and information on the condition of trees in six locations of Metro Urban Forest are not yet available. Therefore, this study was conducted to assess tree damage in each Metro Urban Forest. Evaluation of tree damage such as location, type, and level of tree damage was conducted for each tree in accordance with the damage criteria of the Forest Health Monitoring method. Data were then analyzed by calculating the damage index and tree damage level index. The results showed that the vegetation in Metro Urban Forests was dominated by trees with the healthy condition of 1.549 trees or 87% of the total trees, hence the Metro Urban Forests could be considered safe for visitors. The level of tree damage in each Metro Urban Forest is as follows: 3% in Islamic Center Urban Forest, 9% in Tesarigaga Urban Forest, 12% in Bumi Perkemahan Urban Forest, 13% in Linara Urban Forest, 23% in Terminal 16c Urban Forest, and 23% in Stadion Urban Forest at 23%. Overall tree damage in the Metro Urban Forest reached 232 trees or 13% of the total trees. Tree maintenance in each urban forest in Metro City is needed to maintain tree health, the safety of visitors, and improve the quality of the urban environment. Keywords: damaged trees, Forest Health Monitoring, Metro Urban Forests